(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This work is devoted to the preparation and investigation of a composite based on styrene–butadiene–styrene (SBS) polymer using carbon nanotubes. Nanocomposites based on styrene–butadiene–styrene polymer (SBS) and carbon nanotubes were prepared by the emulsion mixing method, while the vulcanization process was carried out in accordance with standard test methods used for SBS evaluation. The incorporation of carbon nanotubes (CNTs) into the rubber compound improved the compatibility of the components, and the resulting nanocomposite exhibited high thermal stability. The nanomaterial enhanced the process ability of SBS rubber–based composites. Compared with rubber reinforced solely with carbon black, the use of nanomaterials led to a 27% increase in stress at 100% permanent elongation. In addition, partial replacement of carbon black resulted in an increase in the elongation at break of the vulcanization from 424.5% to 554.0%. The mechanical properties of the obtained rubbers demonstrated that they can be regulated by